THE IMPACT OF THE UTAUT2 APPROACH TO NEW FINANCING TECHNOLOGIES AND ITS CHALLENGES IN LIGHT OF THE CORONA PANDEMIC ON THE BEHAVIOR OF INDIVIDUALS - Mustafa S. Abdulreza; Hussein Mohammed Ali; Janan Abdel Abbas Ismail; Hayder M. Kareem Alduhaidahawi (Scholar Express Journals, 2024)
This research mainly sought to clarify the role and importance of the financial technology model for new financing techniques in banking, as it is one of the modern concepts in the financial arena, which seeks through banks, especially Iraqi ones, to benefit from their innovations in light of health crises, health ban restrictions, and the lack of access to banking services. In the traditional manner, this is what prompted banks to use these means to provide electronic services and to benefit from these innovations in providing electronic banking services characterized by high quality, which contributes to meeting the market need and keeping pace with the developments taking place today in the financial and business sector, and thus trying to influence the behavior of individuals in accepting these technologies. The research relied on the descriptive analytical approach in studying the various aspects of the new financing techniques model and individual behavior, and testing the research hypothesis by making a questionnaire of 51 items, which was analyzed according to the SPSS statistical program. The problem of the research lies in demonstrating the effect of using the new financing techniques model. According to financial technology in changing the behavior of individuals in light of the presence of health crises, especially the Corona crisis, on the basis of which the alternative hypothesis was accepted, the research reached the conclusion that there is a great acceptance by individuals towards new financing techniques and financial technology innovations in light of health crises and the inability to obtain... On services through banking branches, the research also reached a number of recommendations, the most important of which is that Iraqi banks employ financial technology innovations in providing banking services with distinctive specifications that enable individuals to obtain them without the need to access banking branches
Keywords: UTAUT2; Financing Technologies and behavior; individuals